Development of Video Tutorials for Solving Problems on Temperature and Heat Topic to Enhance Students' Cognitive Skills - Rinda Harjuna; Agus Suyudi; Sulur Sulur; Endang Sriwati (Jurnal Riset Pendidikan Fisika, 2022)
The recent transformation into online learning has reduced students’ cognitive abilities, as indicated by their difficulty in solving problems, including physics questions. Teachers tend to give assignments to work on questions without examples to solve those problems. Based on interview questionnaires, students have difficulty working on physics questions. The purpose of this research is to develop a video tutorial product to solve question items and to find out the products’ feasibility and readability from the students’ perspective. This study used Research and Development with a 4D research design. The video tutorial product was then validated by expert lecturers and resulted in an average score of 3.79 (valid). After being declared valid, then a trial was carried out on class XI students of the 2020/2021 academic year to determine the feasibility and readability of the product. The results of the limited trial showed a feasibility value of 85.0% and the readability value of 90.76%. Since the obtained feasibility and readability scores were above 80%, so the video tutorial product is categorized as successful and can be used as a learning companion media.Keywords: Video Tutorial, Cognitive Skills, Problem Solving ABSTRAKPerubahan pembelajaran secara daring membuat kemampuan kognitif peserta didik mengalami penurunan, yang ditunjukkan oleh kesulitan dalam  memecahkan permasalahan salah satunya yaitu soal-soal  fisika. Guru cenderung memberikan tugas untuk mengerjakan soal-soal, tetapi tanpa disertai contoh untuk menyelesaikan soal. Berdasarkan angket wawancara, peserta didik mengalami kesulitan mengerjakan soal-soal fisika. Tujuan penelitian ini yaitu untuk mengembangkan produk video tutorial penyelesaian soal dan mengetahui kelayakan dan keterbacaan produk oleh peserta didik. Metode yang digunakan adalah Penelitian dan Pengembangan dengan desain penelitian 4D. Produk video tutorial kemudian dilakukan uji validasi oleh dosen ahli dan menghasilkan nilai rata-rata 3,79 (valid). Setelah dinyatakan valid, kemudian dilakukan uji coba kepada peserta didik kelas XI tahun ajaran 2020/2021 untuk mengetahui kelayakan dan keterbacaan produk. Hasil yang diperoleh dari uji coba terbatas yaitu nilai kelayakan sebesar 85,0% dan nilai keterbacaan sebesar 90,76%. Hasil uji kelayakan dan keterbacaan yang diperoleh mendapt hasil di atas 80%, maka produk video tutorial sudah dapat dikatakan berhasil dan dapat digunakan sebagai media pendamping belajar.